Proteinuria Is an Independent Risk Factor for First Incident Stroke in Adults Under Treatment for Hypertension in China - Chunyan Zhang; Xiaobin Wang; Mingli He; Xianhui Qin; Genfu Tang; Xin Xu; Yu Wang; Yong Huo; Yefeng Cai; Jia Fu; Gang Zhao; Qiang Dong; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2015)
Background Conflicting evidence exists regarding whether reduced estimated glomerular filtration rate (eGFR) and proteinuria are independent risk factors for stroke and its subtypes in hypertensive patients. This study investigated the association of these renal measures with first incident stroke in adults under treatment for hypertension in China. Methods and Results The study included 19 599 adults aged 45 to 75 years who participated in the China Stroke Primary Prevention Trial. Baseline eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration creatinine equation. Proteinuria was assessed by qualitative dipstick urinalysis and in a subset by the quantitative albumin–creatinine ratio method. Cox regression analysis was used to examine the effects of eGFR and proteinuria on the risk of first incident stroke. During a median of 4.5 years of follow‐up, a total of 585 first strokes (472 ischemic strokes) were identified. Compared to participants without proteinuria, participants with proteinuria (trace or more by dipstick) had a 35% increased risk of first stroke: the adjusted hazard ratio (HR) (95% CI) was 1.35 (1.09–1.66, P=0.005). The results were robust in subgroup analyses. In a subset with data on proteinuria measured by quantitative albumin–creatinine ratio, a similar association was found. In both independent and combined analyses with proteinuria, eGFR was not significantly associated with stroke. Conclusions In adults under treatment for hypertension in China, baseline proteinuria measured by dipstick or quantitative albumin–creatinine ratio, but not reduced eGFR, was found to be an independent risk factor for first incident stroke and ischemic stroke.